If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=-3(b+-24)
We move all terms to the left:
9-(-3(b+-24))=0
We add all the numbers together, and all the variables
-(-3(b-24))+9=0
We calculate terms in parentheses: -(-3(b-24)), so:We get rid of parentheses
-3(b-24)
We multiply parentheses
-3b+72
Back to the equation:
-(-3b+72)
3b-72+9=0
We add all the numbers together, and all the variables
3b-63=0
We move all terms containing b to the left, all other terms to the right
3b=63
b=63/3
b=21
| 8=(3x-4) | | 6/11x=8/11 | | 0.19y=0.589 | | 2x÷6=12 | | (-11+2b)=11+2b | | d/4-7=- | | -6+4(1-6m)=190 | | 5=(3x-4) | | -(4-c)=(4-c) | | -x/3+5=-9 | | -8(-x-3)=-8x-3 | | k+25/6=9 | | 4-3x=21x | | k/8+36=38 | | 3(-5x+10)=30 | | p-2(-3-6p)=-85 | | -5*(36k)^(3/2)=-1080 | | 5z-2=11 | | 3+5a=8–40a+6 | | 6x+5=29* | | 22y-72=0 | | -14+6b+7-2b=1+7b | | -2+3/8x=6 | | 6x(x)=1,176 | | x+6-2×=x-24 | | -8x+1=5(x+1)-13(x-3) | | (x)(x)(6)=1,176 | | 10(3x+3)=20-30+628x2 | | 16y=18•y-1 | | -20n-15=-15-20n | | -6x+13=19 | | .10x+0.15(50–x)=0.12(50) |